Juridical Analysis Of Granted Proprietary Right To The Church As Christian Organization (Christian Church Study In Semarang) - Kezia Resiocta Sehati (Semarang State University Undergraduate Law and Society Review, 2025)
The church as a legal subject as well as a place of Christian worship that has a role and function as a place of worship for Christians. The granting of property rights over land to Christian religious institutions, namely churches, provides an important issue in the land system in Indonesia. The granting of property rights aimed at the church as a Christian religious institution does not necessarily transfer its status directly, but the granting of property rights to the church according to applicable regulations must be stated with written evidence in the form of a decision from the authorized official to appoint the church and the church must submit an application for property rights to be able to get land with property rights status. Government Regulation no. 38 of 1963 concerning the Appointment of Legal Entities that can have Property Rights to land jo SK / 22 / HK / 1969 dated concerning the Appointment of the Protestant Church Body in Western Indonesia as a Legal Entity that can have Property Rights. As applicable regulations regarding the granting of property rights by the Church, regulatory affirmation is needed so that the process of granting property rights can be carried out fairly, effectively and in accordance with applicable legal principles.